Development of STEM-Based E-Modules Integrated with Ethnoscience to Improve Creative Thinking Skills in Biotechnology Materials for Grade X Students - Amelia, Suhaila; Khairuna, Khairuna (Universitas Negeri Semarang, 2025)
Creative thinking skills are part of the 21st century skills that need to be mastered and developed. Therefore, innovative teaching materials are needed that can help develop creative thinking skills. This development research aims to produce teaching materials in the form of STEM-based e-modules integrated with ethnoscience that are feasible, practical, and effective for students and teachers. The instruments used are needs analysis in the form of teacher interview guidelines and teacher and student needs questionnaires, material and media expert validation sheets, and practicality sheets. Then the effectiveness sheet in the form of pretest and post-test sheets. Based on the results of data analysis, media validation scored 99.2%, material validation results scored 88.23%, teacher response questionnaire results scored 98%, and student response questionnaire results scored 93.26%. The effectiveness assessment resulted in an average N-Gain score of 0.83 which is included in the highly criteria. Therefore, it can be concluded that this ethnoscience-integrated STEM-based e-module is feasible, practical, effective, and can facilitate the development of students’ creative thinking skills.